2009
DOI: 10.1105/tpc.109.070771
|View full text |Cite
|
Sign up to set email alerts
|

A Zinc Finger Transcription Factor ART1 Regulates Multiple Genes Implicated in Aluminum Tolerance in Rice  

Abstract: Aluminum (Al) toxicity is the major limiting factor of crop production on acid soils, but some plant species have evolved ways of detoxifying Al. Here, we report a C2H2-type zinc finger transcription factor ART1 (for Al resistance transcription factor 1), which specifically regulates the expression of genes related to Al tolerance in rice (Oryza sativa). ART1 is constitutively expressed in the root, and the expression level is not affected by Al treatment. ART1 is localized in the nucleus of all root cells. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
351
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 355 publications
(365 citation statements)
references
References 43 publications
(61 reference statements)
7
351
2
5
Order By: Relevance
“…The primary Al avoidance mechanism involves exclusion of Al from the growing root tip via the exudation of Al-chelating OAs into the rhizosphere, where the OAs form nontoxic OA-Al complexes which do not enter the root. Over the past decade, some key cellular/molecular components for both the Al tolerance and exclusion mechanisms have been identified in plants (6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…The primary Al avoidance mechanism involves exclusion of Al from the growing root tip via the exudation of Al-chelating OAs into the rhizosphere, where the OAs form nontoxic OA-Al complexes which do not enter the root. Over the past decade, some key cellular/molecular components for both the Al tolerance and exclusion mechanisms have been identified in plants (6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Rice, which is the most aluminumresistant cereal crop, employs multiple strategies to achieve high aluminum resistance. The rice aluminum stress-responsive transcriptional factor, ART1, regulates expression of 31 downstream genes (Yamaji et al, 2009). In addition to gene-based aluminum tolerance strategies, some external factors can also affect aluminum resistance, such as external phytohormone application.…”
mentioning
confidence: 99%
“…The difference in Al-induced secretion in different plant species may be attributed to the expression level of these MATE genes although the exact mechanisms regulating the gene expression is unknown. Recently, a C2H2-type zinc finger transcription factor, STOP1 in Arabidopsis and ART1 in rice (Iuchi et al 2007;Yamaji et al 2009), which regulate AtMATE and OsFRDL2, respectively, have been identified (Liu et al 2009;Yamaji et al 2009). Identification of similar transcription factor in rye may help understand the molecular mechanism of Al tolerance in rye and difference in organic acid secretion between different species.…”
Section: Discussionmentioning
confidence: 99%
“…Following primers, which were designed based on the sequences of HvAACT1 and OsFRDL2 (Furukawa et al 2007;Yamaji et al 2009), were used to amplify fragments from rye cDNA by PCR; 5 0 -ACGGTGGTGCTTGGTCTCTT-3 0 (forward) and 5 0 -CAGG TGCTAGCTACGGTCCTG-3 0 (reverse) for ScFRDL1, 5 0 -TGC ATCAATGGCTGCACGGC-3 0 (forward) and 5 0 -GCAGTCC CTATCCTTAAGAATCCTGC-3 0 (reverse) for ScFRDL2. The fragmentary PCR products were cloned into pGEM-T-Easy vector and the sequences were determined (ABI3130 Genetic Analyser; Applied Biosystems, Foster City, CA, USA).…”
Section: Cloning Of Mate Genes From Ryementioning
confidence: 99%